(untitled) (LACCEI, 2024)
Abstract – This article presents the automation of a fruit label dispensing system using a PLC programmable logic controller. The finite state machine method is used for system design and programming, Boolean algebra and Karnaugh maps allow us to simplify the transition table of a Moore-type state machine. These methods allow for a simplified implementation process for the Ladder language, industry standard IEC 61131-3. The experimental results, carried out in a prototype, validated the proposal in an acceptable way, allowing to label the fruits that the process transports.